2008
DOI: 10.1002/jnr.21900
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying Li+ effects in glutamatergic and GABAergic neurotransmissions in the adult rat brain and in primary cultures of neural cells as revealed by 13C NMR

Abstract: We investigated by (13)C nuclear magnetic resonance (NMR) the mechanisms underlying Li(+) effects on glutamatergic and GABAergic neurotransmission systems in the adult rat brain and in primary cultures of cortical neurons and astrocytes during the metabolism of (1-(13)C) glucose or (2-(13)C) acetate. Adult male rats receiving a single dose of Li(+) intraperitoneally (7 mmol/kg) were infused 2 hr later, for 60 min, with (1-(13)C) glucose (80 mumol/min/kg) or (2-(13)C) acetate (240 micromol/min/kg). High-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our results revealed that 15 mmol L -1 Li + caused a statistically significant decrease in glucose uptake by neurons but no apparent effects in glucose or acetate uptake by astrocytes. The decrease in neuronal glucose uptake in the presence of Li + , consistent with an inhibition of the glycolytic flux, was not paralleled by a concomitant significant change in lactate production, indicating that the decreased glucose consumption reflects a net decrease in glucose oxidation and TCA cycle activity (Fonseca et al, 2009). The ability of Li + to decrease glycolytic and TCA cycle fluxes is in agreement with the results obtained for SH-SY5Y cells (Fonseca et al, 2005) and other data in the literature (Abreu & Abreu, 1973;Kajda & Birch, 1981;Nordenberg et al, 1982).…”
Section: + Effects On the Metabolic Balances In Cortical Astrocytementioning
confidence: 92%
See 4 more Smart Citations
“…Our results revealed that 15 mmol L -1 Li + caused a statistically significant decrease in glucose uptake by neurons but no apparent effects in glucose or acetate uptake by astrocytes. The decrease in neuronal glucose uptake in the presence of Li + , consistent with an inhibition of the glycolytic flux, was not paralleled by a concomitant significant change in lactate production, indicating that the decreased glucose consumption reflects a net decrease in glucose oxidation and TCA cycle activity (Fonseca et al, 2009). The ability of Li + to decrease glycolytic and TCA cycle fluxes is in agreement with the results obtained for SH-SY5Y cells (Fonseca et al, 2005) and other data in the literature (Abreu & Abreu, 1973;Kajda & Birch, 1981;Nordenberg et al, 1982).…”
Section: + Effects On the Metabolic Balances In Cortical Astrocytementioning
confidence: 92%
“…(Fonseca et al, 2009). Values are means ± SEM for the number (n) of experiments indicated in parentheses.…”
Section: + Effects On the Metabolic Balances In Cortical Astrocytementioning
confidence: 99%
See 3 more Smart Citations